Surfactant as an additive for producing cellulosic sugar from wood residue - Tu, Wei-Lin; Ou, Chung-Mao; Guo, Gia-Luen; Chao, Yu (Bioresources, 2019)
Due to environmental concerns and the proposed global policies for reducing carbon emissions, lignocellulosic biomass is an attractive renewable feedstock for biofuel and biochemical production. Wood residues from the plywood industry have a lignin content as high as 30.7% ± 0.1%. Diluted acid pretreatment followed by enzymatic hydrolysis is often employed to release sugar from lignocellulosic biomass. A high lignin content limits the accessibility of cellulose. Lignin also binds with enzymes, which reduces the enzymatic hydrolysis efficiency. In this study, different concentrations of polyethylene glycol (PEG) 6000 were used as an additive to inhibit the detrimental effects caused by lignin. The optimal dosage was 1 g/L, which increased the glucose production to 35.8% and 26.6% for solid-to-liquid ratios of 2% and 20%, respectively. The results suggest that PEG 6000 is a suitable potential additive for increasing the bioethanol production from plywood residue in upscale operations.